On following pages: 3. Peale's Dolphin (Lagenorhynchus australis); 4. Hourglass Dolphin (Lagenorhynchus crucigen; 5. Pacific White-sided Dolphin (Lagenorhynchus obliquidens); 6. Dusky Dolphin (Lagenorhynchus obscurus); 7. Irrawaddy Dolphin (Orcaella brevirostris); 8. Australian Snubfin Dolphin (Orcaella heinsohni). in Delphinidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
On following pages: 3. Peale's Dolphin (Lagenorhynchus australis); 4. Hourglass Dolphin (Lagenorhynchus crucigen; 5. Pacific White-sided Dolphin (Lagenorhynchus obliquidens); 6. Dusky Dolphin (Lagenorhynchus obscurus); 7. Irrawaddy Dolphin (Orcaella brevirostris); 8. Australian Snubfin Dolphin (Orcaella heinsohni). Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Delphinidae, pp. 410-526 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 489, DOI: 10.5281/zenodo.6610922